PENGEMBANGAN PARIWISATA BERKELANJUTAN DI D.I.YOGYAKARTA MELALUI PENDEKATAN KEWIRAUSAHAAN SOSIAL (SOCIOPRENEURSHIP) - Aisyianita, Revi Agustin (STP AMPTA Yogyakarta, 2017)
Sociopreneurship or called as a social entrepreneurship is a new breakthrough on tourism development activities. Principle’s of social entrepreneur parallel with sustainable tourism development which empowerment became one of a element (santosa, 2007). pay attention to the sustainability natural resources, human resources, culture and consider economic benefit. Social entrepreneurship is one of implementation sustainable tourism development because sociopreneur not only pay attention to profit but also concern on social and environmental benefit. The growth of tourism social entrepreneurship in Yogyakarta is driven by the iniative from individu or small groups from community who want to solve social problem through tourism. Social entrepreneurship parallel with sustainable tourism principle, which community participant is main factor development activities. D.I Yogyakarta already has enough amount of sociopreneur, but it has a few little amount sociopreneur who engaged in tourism development.Some of tourism sociopreneur in D.I Yogyakarta, such as : Desa Wisata Gunung Api Purba Nglanggeran, House of lawe, and DIfa City Tour has proven how sociopreneurship bring significant change for community. Desa Wisata Gunung Api Purba Nglanggeran plays an important role in improving social welfare community in the tourist area, House of lawe plays an important role in women empowerment, and DifaCity Tour plays an important role on empowerment person with disabilities. Keyword : sociopreneur, social entrepreneurship, sustainable tourism.